Paclitaxel-Coated Balloons for the Treatment of Symptomatic Central Venous Stenosis in Vascular Access: Results From a European, Multicenter, Single-Arm Retrospective Analysis. (June 2021) - Kitrou, Panagiotis M.; Steinke, Tobias; El Hage, Rami; Ponce, Pedro; Lucatelli, Pierleone; Katsanos, Konstantinos; Spiliopoulos, Stavros; Spinelli, Alessio; Bisdas, Theodosios; Stavroulakis, Konstantinos; Jaffer, Ounali; Mallios, Alexandros; et al.
Introduction: This was a European, multicenter, investigator-initiated and run, single-arm retrospective analysis to assess the safety and the clinical benefit of the use of paclitaxel-coated balloon (PCB) for the treatment of symptomatic central venous stenosis (CVS). Materials and Methods: Eleven centers from 7 countries across Europe, submitted 86 cases performed during the period between October 2015 and June 2018. Minimum follow-up was 6 months. Patient baseline demographics and procedural details were collected. Mean age was 62.6 years (SD 15.2 years). Median vascular access age was 3.0 years (IQR 1.2–4.8 years). A total of 55 were arteriovenous fistulas (64%) the rest arteriovenous grafts (31/86, 36%). Vessels treated were 43 subclavian veins, 42 brachiocephalic veins and 1 superior vena cava. Median drug-coated balloon diameter was 10 mm (IQR 8–12 mm). Primary outcome measures were clinically assessed intervention-free period (IFP) of the treated segment at 6 months and procedure-related minor and major complications. Secondary outcome measures included access circuit survival, patient survival, and the investigation of independent factors that influence the IFP. Results: IFP was 62.7% at 6 months. Median patient follow-up time was 1.0 year (IQR 0.5–2.2 years). There was 1 minor complication (1/86; 1.2%) and no major complications. Access circuit survival was 87.7% at 6 months. Patient survival was 79.7% at 2 years according to Kaplan-Meier survival analysis. Higher balloon diameters significantly favored IFP [HR 0.71 (0.55–0.92), p=0.006; 5–7 mm group vs 8–12 mm group, p=0.025]. Conclusion: In this analysis, use of PCBs for the treatment of symptomatic CVS was safe. Efficacy was comparable to previous trials. Increased balloon size had a significant effect on patency rates.